FRI0164 T Cells Expansion in Rheumatoid and Psoriatic Arthritis Patients under anti-TNF-alpha Agents. (15th July 2016) - Picchianti-Diamanti, A.; Rosado, M.M.; Pilozzi, E.; Markovic, M.; D'Amelio, R.; Laganà, B.
Abstract : Background: An increased risk for lymphoproliferative disorders, specially Hodgkin's and non- Hodgkin's lymphoma has been reported in Rheumatoid Arthritis (RA) and Psoriatic Arthritis (PsA) patients.Several factors such as the genetic background, the persistent stimulation of T and B cells by unknown antigens and immunosuppressive therapies can be involved in increasing the risk of malignancies in these patients. A role for anti- TNF-α therapy is still controversial Objectives: To analyse the induction of lymphocytosis in RA and PsA patients under anti-TNF-α therapy and explore its possible malignant evolution Methods: RA and PsA patients under anti-TNF-alpha therapy that presented a de novo lymphocytosis (circulating lymphocytes >3400 cells/μl for at least 3 months) were evaluated for lymphocyte subpopulations: total T cells (CD3+), T helper (CD3+CD4+CD45+), T suppressor (CD3+CD8+CD45+), natural killer (CD16+CD56+CD45+) and B cells (CD19+CD45+). Molecular analysis of the T Cell Receptor (TCR) was also performed as follow: total DNA was extracted from PB using Qiagen DNA Kit Extraction; molecular evaluation of TCRγ gene rearrangements was performed using a multiplex PCR with fluorescent labelled oligonucleotides; PCR reactions for TCRγ gene were carried out using "TCRγ rearrangements molecular analysis kit" and amplifications products analyzed on a 3130 Genetic Analyzer. The lengths of the Vγ1–8/Jγ1·3/2·3 and Vγ1–8/Jγ1·1/2·1 PCR products were 145–230 base pairs (bp) and 230–255bp, respectively. Samples were scored as monoclonal if one unequivocal peak in the expected range was observed Results: 25/208 patients (12%) (15 RA and 10 PsA) showed a de novo appearance of a mild persistent lymphocytosis (from 2800 to 4000 mean cells/ul; p<0.001). 11 patients were treated with Etn, 7 with Ada, 4 with Ifx and 3 patients with Gol. The analysis of PBL subsets revealed that B and NK cells were not the cause for the lymphocytosis because the distribution of these populations was at the lowest limit of the normal range (9.6% and 10% respectively). In contrast, we observed a mild increase in the mean percentage of CD3+CD4+ cells (51%). TCRγ gene rearrangement showed a polyclonal distribution in 11 patients (44%), oligoclonal in 9 patients (36%), whereas in 5 patients (20%) we observed the predominance of a monoclonal peak. Lymphnodes ultrasonography did not reveal any sign of malignant proliferation. Despite of this result in the absence of clear guidelines we decided to interrupt the biological therapy in these 5 patients to reduce the risk of developing malignancy. Three months after biological suspension a significant decrease in the total lymphocyte count was observed (mean value from 4134 to 3168cells/μl; P<0.008), whereas TCRγ repertoire maintained its monoclonality Conclusions: We observed in both RA and PsA a de novo appearance of lymphocytosis in a relevant percentage of patients within which five showed the emergence of a single TCR clone. Strict follow-up of the RA and PsA disease activity and of TCR diversity evolution will allow the early detection of lymphoma or the re-establishment of TCR diversity thus permitting the application of a more targeted therapy Disclosure of Interest: None declared